2022
DOI: 10.3389/fonc.2022.916839
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights Into Mesothelioma Therapy: Emerging Avenues and Future Prospects

Abstract: Malignant mesothelioma is a rare and aggressive cancer that develops in the thin layer surrounding the mesothelium and is mainly caused by asbestos exposure. Despite improvements in patient prognosis with conventional cancer treatments, such as surgery, chemotherapy, and radiotherapy, there are still no curative treatment modalities for advanced disease. In recent years, new therapeutic avenues have been explored. Improved understanding of the mechanisms underlying the dynamic tumor interaction with the immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 139 publications
0
25
0
Order By: Relevance
“…The standard treatment for unresectable PM consists of the combination of cisplatin and pemetrexed, which, however, has not proved to be resolutive and only partially improves the patients’ quality of life [ 2 , 6 ]; consequently, novel therapeutic strategies are needed. We have previously demonstrated that GHRH antagonists MIA-602 and MIA-690 alone exert potent and similar antitumor effects in vitro, in human PM cell lines and primary cells, and in vivo, in a xenograft model of human PM [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The standard treatment for unresectable PM consists of the combination of cisplatin and pemetrexed, which, however, has not proved to be resolutive and only partially improves the patients’ quality of life [ 2 , 6 ]; consequently, novel therapeutic strategies are needed. We have previously demonstrated that GHRH antagonists MIA-602 and MIA-690 alone exert potent and similar antitumor effects in vitro, in human PM cell lines and primary cells, and in vivo, in a xenograft model of human PM [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, our present results show that MIA-690 potentiates the effect of cisplatin/pemetrexed in PM xenografts also on inhibition of NF-kB, assessed as phosphorylation of p65 subunit, and STAT3 phosphorylation. The activation of NF-kB is involved in inflammatory pathways and associated with exposure to asbestos fibers and tumor evolution in mesothelioma [ 2 ]. Furthermore, the transcription factor STAT3, which controls the expression of genes regulating survival, proliferation and self-renewal, is frequently activated in many cancers, including mesothelioma, and is associated with oncogenic characteristics and poor survival [ 2 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations